Students' Learning Preferences and Instructional Adaptation In Islamic Religious Education At SMK Negeri 3 Medan: A Qualitative Study - Dela Fahiran Pandiangan; Ali Imran Sinaga (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
Background: Conventional lectures often cause fragmented attention among vocational students. Objective: This study explored students' learning preferences and instructional adaptations in Islamic Religious Education (PAI) classrooms at SMK Negeri 3 Medan. Methods: A qualitative descriptive case study was conducted from February 27 to June 18 (AY 2025/2026). One experienced teacher and three eleventh-grade Pharmacy students were selected via purposive sampling. Data were gathered through 5× classroom observations, 4× semi-structured interviews (12–30 minutes), and lesson plan analysis, then analyzed using Miles, Huberman, and Saldana's interactive model with manual coding. Trustworthiness was ensured via triangulation, member checking, peer debriefing, and audit trails. Findings: Students preferred practical, hands-on activities and audiovisual media over fixed learning styles, contextually shaped by the procedural nature of Islamic rituals and vocational learning-by-doing habituation. Instructional adaptations, such as short moral videos and ability-based reading groups, effectively enhance student engagement and classroom focus. Conclusion: Creative adaptations temporarily boosted student interest but could not eliminate structural constraints like weak parental reinforcement at home. Implications: Instructors should flexibly blend practical, visual, auditory, and reflective activities within a single flow rather than labeling students into rigid categories.